Effect of pre-treatments on drying, rehydration, and color characteristics of red pepper ('Charliston' variety) - Doymaz, Ibrahim; Kocayigit, Fergun (KOREAN SOCIETY FOOD SCIENCE & TECHNOLOGY-KOSFOST, 2012)
The drying characteristics of red pepper were examined in convection dryer at a temperature range of 55-70A degrees C with a constant air velocity of 2 m/s. The red peppers were pre-treated with ethyl oleate and citric acid solutions before drying process. Drying process continued until sample moisture fell down to 0.12 kg water/kg d.m. It was observed that drying, rehydration, and color characteristics were significantly influenced by air temperature and pretreatments. Moisture transfer from red peppers was described by applying the Fick's diffusion model, and the effective moisture diffusivity was calculated. The effective moisture diffusivity ranged from 5.72x10(-10) to 1.75x10(-9) m(2)/s for the studied temperature range. The values of activation energy (E (a)) were 50.27, 49.21, and 48.45 kJ/mol for control, pre-treated with citric acid, and ethyl oleate, respectively. Drying data was fitted to 4 drying models, and the best models were logarithmic and Page.
Keywords: activation energy; color; drying; effective moisture diffusivity; pre-treatment; red pepper; rehydration capacity; MOISTURE DIFFUSIVITY; DEHYDRATION KINETICS; QUALITY; GREEN; BEHAVIOR; SLICES; ENERGY; SOLAR; Food Science & Technology